Pengaruh Gaya Kepemimpinan Demokratis Kepala Sekolah Terhadap Kinerja Guru PAUD - Sari, yunita -; Khosiah, Siti; Maryani, Kristiana (Jurnal Golden Age, 2020)
ABSTRACT: The performance of teachers is one of the success factors of the school. Advance and retreat of school are determined by the performance of individual teachers in the school. In improving the teacher’s performance, it takes the role of the principal is using his leadership style. Principal’s who use the democratic leadership style is open so that it can improve the performance of teachers and the achievement of objectives together. The principal’s democratic leadership style is thought to influence the teacher’s performance. This study aims to determine the effect of the influence of the principal’s democratic leadership style on the teacher’s performance of PAUD in Anyar, Serang-Banten. This research uses the Ex Post Facto method. Data collection techniques for variables the principal's democratic leadership style and teacher performance of PAUD using a questionnaire (questionnaire), which is given to 17 teacher respondents in Anyar, Serang-Banten Data analysis technique using product moment Pearson correlation analysis, Based on the results of research shows the correlation coefficient between variables the principal democratic leadership style on teacher performance of 0.627 means there is an influence between the influence principal's democratic leadership on the teachers performance of PAUD Anyar, Serang-Banten.